2023
DOI: 10.3390/biomedicines11051249
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Tissue Mobilization and Pain Neuroscience Education for Chronic Nonspecific Low Back Pain with Central Sensitization: A Prospective Randomized Single-Blind Controlled Trial

Abstract: This study was conducted to demonstrate the therapeutic effect of soft-tissue mobilization (STM) combined with pain neuroscience education (PNE) for patients with chronic nonspecific low back pain with central sensitization. A total of 28 participants were recruited and randomly allocated to either the STM group (SMG) (n = 14) or the STM plus PNE group (BG; blended group) (n = 14). STM was applied twice a week for four weeks, with a total of eight sessions, and PNE was applied within four weeks, for a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…The researchers attributed this effect to the Fear Avoidance Model applied as PNE [50], which effectively reduced levels of kinesiophobia by explaining anxiety, fear, avoidance due to fear, and their consequences for pain experience. Our research results also align with the findings of Song et al [13], who identified a significant reduction in the TSK and PCS scores by adding PNE to a four-week manual therapy program for patients with CNLBP. However, it is worth noting that the improvements identified in our study were greater for both scores (TSK and PCS) compared to this research.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The researchers attributed this effect to the Fear Avoidance Model applied as PNE [50], which effectively reduced levels of kinesiophobia by explaining anxiety, fear, avoidance due to fear, and their consequences for pain experience. Our research results also align with the findings of Song et al [13], who identified a significant reduction in the TSK and PCS scores by adding PNE to a four-week manual therapy program for patients with CNLBP. However, it is worth noting that the improvements identified in our study were greater for both scores (TSK and PCS) compared to this research.…”
Section: Discussionsupporting
confidence: 91%
“…The objective of this clinical study was to examine the effectiveness of a manual therapy protocol in conjunction with the provision of PNE with integrated MI. Compared to other studies that similarly applied combined manual therapy and PNE protocols in individuals with CNLBP [12,13,42,43], the innovation of our study was the integration of the MI component in PNE. We hypothesized that the addition of MI to PNE in a manual therapy program could increase the positive effects and provide more long-term results related to the application of manual therapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another perspective to consider is the psychological aspect of pain and disability. It's established in literature that pain cognition is multi-dimensional, encompassing not only the physical but also emotional, cognitive, social factors [34,35]. Thus, even if thrust manipulation managed to address the nociceptive component of pain effectively, it may not have dealt with other underlying issues, like fear of movement or re-injury, that contribute to disability [36][37][38].…”
Section: Discussionmentioning
confidence: 99%